Donor-derived carbapenem-resistant Klebsiella Pneumoniae infections leading to retroperitoneal abscesses in kidney transplant recipients: a report of two cases - Xia Gao; Lei Chen; Shunliang Yang; Changyan Zhu; Dong Wang (BMC Infectious Diseases)
Abstract Background Retroperitoneal abscesses caused by donor-derived Carbapenem-Resistant Klebsiella Pneumoniae (CRKP) infections are rare and often challenging to diagnose early due to a lack of specific symptoms. Case presentation In case one, a 64-year-old male presented with unexplained fever and emaciation three months after undergoing a kidney transplant for end-stage renal disease. Metagenomic Next-Generation Sequencing identified CRKP in peripheral blood samples, and CT scans confirmed a retroperitoneal abscess. Considering the infectious status of the donor and other recipients, donor-derived infection (DDI) was suspected. Surgical incision and drainage were performed along with anti-infection treatment and immunosuppressive agents were adjusted. There was no recurrence of infection after a six-month follow-up. In case two, a 45-year-old male was readmitted due to light red pus discharge from the drainage tube fistula on day 32 after undergoing a kidney transplant for end-stage renal disease. A CT scan confirmed a retroperitoneal abscess between the kidney allograft and the spinal column. Based on the culture results of the purulent sample and perfusion fluid from the donor kidney, DDI was suspected, leading to prompt surgical incision and drainage, along with anti-infection treatment. After a five-month follow-up period, no infection recurrence was observed. Conclusions This study reported two cases of retroperitoneal abscesses caused by DDI following kidney transplantation, highlighting the importance of considering donor-derived CRKP infections in transplant recipients presenting with unexplained symptoms. Timely interventions are crucial for effective management and prevention of recurrence.